ANALYSIS OF STUDENT MOTIVATION IN ARABIC LANGUAGE LEARNING BASED ON ARABIC SCRABBLE MEDIA - Shalihah, Imroatus; Zulaini, Nabilla Nurbaiti; Basid, Abdul; Masrokhin, Masrokhin (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2025)
Learning motivation is the key to student success, but learning Arabic is often challenging. This study examines using Arabic Scrabble media as an innovation in Arabic language learning. This research aims to: 1) describe Arabic language learning using Arabic Scrabble media; 2) evaluate the success of using Arabic Scrabble media; 3) understand students' perceptions of Arabic Scrabble. This type of research is descriptive and explanatory with a mixed method (quantitative and qualitative). Data collection was done through interviews, observation, documentation, and questionnaire. Data analysis used Miles and Huberman’s theory in data reduction, data presentation, and conclusion drawing. The results of this study indicate that: 1) the use of Arabic Scrabble media provides benefits in terms of motivation, engagement, and vocabulary understanding; 2) Arabic Scrabble media is more effective when used in small groups; 3) 85% of students confirmed that Arabic Scrabble media is highly effective in vocabulary learning. This research implies that Arabic Scrabble media can be an effective alternative to increase students’ learning motivation in Arabic language learning. Thus, teachers can utilize this media to create a more fun, interactive, and meaningful learning atmosphere.